Investigation of physiological exercise parameters and sleep status of elite karate athletes - Hayirli, Ilknur; Ayar, Ahmet (Annals of Medical Research, 2023)
Aim: The aim of this study was to determine sleep quality and exercise-related physiological parameters (heart rate, heart rate reserve, cardiac output, blood pressure, maximum oxygen uptake capacity) of elite karate athletes.Materials and Methods: Ten athletes, 3 girls and 7 boys, who are interested in karate at an elite level in Trabzon, participated in the study. Anthropometric measurements and body mass index measurements were made. Cardiopulmonary exercise test (CPET) was performed with a gradually increasing intensity (15W/min) bicycle ergometer test protocol. Sleep parameters of the athletes were obtained by using the physical activity measurement holter (Sensewear Armband).Results: The mean age of the individuals was 17.8±1.39 years (n=10), the mean height was 169.0±8.1 cm (n=10), the mean weight was 63.99±7.64 kg (n=10), and the mean body mass index was 22.41 kg/m² (n=10). Average value for oxygen consumption (VO₂) at maximum workload level 43±8 ml/kg/min (n=10, 99±12% of predicted), average maximum power 197±27.50 Watts (n=10, 92%±% predicted) 14), mean minute ventilation (VE) 103±28 L/min (n=10, 95±22% of predicted), mean heart rate (HR) 181±12 beats/min (n=10, 93±7% of predicted) and mean oxygen (O₂) pulse at maximum workload level was 15.20±2.90 ml/beat (n=10, 115.1±17.75% of predicted). The average lying down time of the athletes was 8 hours 8 minutes ±2 hours 26 minutes (n=9), sleep time was 6 hours 9 minutes±2 hours 30 minutes (n=9), and sleep efficiency was 74±12%.Conclusion: The findings of this study show that the participating athletes had a good aerobic capacity and a good training level for the sport branch they were engaged.
Keywords: Aerobic capacity; Exercise; Karate; Sport; Sleep